2015
DOI: 10.1089/chi.2014.0163
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obesity Empowerment Model Group Medical Visits (POEM-GMV) as Treatment for Pediatric Obesity in an Underserved Community

Abstract: POEM-GMV may be a useful approach in the treatment of pediatric obesity in an underserved community. There were statistically significantly improved outcomes in obesity, especially for boys. Significant improvement was observed in many lifestyle factors associated with obesity. Weight loss most closely correlated with reduced stress levels and sugary beverage consumption. Additional studies are needed to further evaluate the efficacy of POEM-GMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Previous publications on SMAs and group visits involved only 1 or 2 providers: a physician, dietician, psychologist, or therapist. [5][6][7][8][9][10][11][12][13][14] In addition, most commercial diet programs do not have pharmacist or physician involvement, although there are some programs available with medical monitoring. The providers for the present study's SMA included a pharmacist, dietitian, and family practice physician.…”
Section: Discussion and Practice Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications on SMAs and group visits involved only 1 or 2 providers: a physician, dietician, psychologist, or therapist. [5][6][7][8][9][10][11][12][13][14] In addition, most commercial diet programs do not have pharmacist or physician involvement, although there are some programs available with medical monitoring. The providers for the present study's SMA included a pharmacist, dietitian, and family practice physician.…”
Section: Discussion and Practice Implicationsmentioning
confidence: 99%
“…The visits were run by a physician, dietician, or staff, and patients in these trials had a significant reduction in their BMI or body fat. [8][9][10] Another trial evaluated focus groups of patients participating in SMAs on managing overweight/ obesity for veterans everywhere, a metabolic assistance group intervention clinic, and smoking cessation at a Veterans Affairs Medical Center. Patients in that trial reported high levels of satisfaction with SMAs and improved self-management skills, overall health, and well-being.…”
mentioning
confidence: 99%
“…The Pediatric Obesity Empowerment Model-Group Medical Visits (POEM-GMV) program examined the use of empowerment in children (average age of 10 years) who were overweight or obese [42]. This study showed that empowerment was effective in terms of reducing the body weight, especially in boys [42].…”
Section: The Effects Of Empowerment Therapy In Type 2 Diabetes Andmentioning
confidence: 99%
“…The Pediatric Obesity Empowerment Model-Group Medical Visits (POEM-GMV) program examined the use of empowerment in children (average age of 10 years) who were overweight or obese [42]. This study showed that empowerment was effective in terms of reducing the body weight, especially in boys [42]. Moreover, improvement in BMI was accompanied by reduced stress levels, increased physical activity, improved diet, and reduction of watching TV [42].…”
Section: The Effects Of Empowerment Therapy In Type 2 Diabetes Andmentioning
confidence: 99%
See 1 more Smart Citation